Women and Economic Activities in Late Medieval Ghent - Hutton, S. author. aut Link
XVI, 240 p. 17 illus.
Keywords: Contrary to the widespread view that women exercised economic autonomy only in widowhood, Hutton argues that marital status was not the chief determinant of women's economic activities in the mid-fourteenth century and that women managed their own wealth to a far greater extent than previously recognized.